Management Accounting Information System Quality, Job Motivation and Managerial Performance - Nabila Nur Alsyifa; Rini Lestari; Andhika Anandya (Universitas Islam Bandung, 2023)
AbstractEvery work performed by the workforce must have good performance so that the company can develop and run effectively. Therefore, someone who occupies a manager's position is expected to be able to produce a good managerial performance to create a company's competitive advantage. Many factors can affect managerial performance including the quality of management accounting information systems and work motivation. The purpose of this study was to find out how much influence the quality of management accounting information systems and work motivation has on the managerial performance of managers in 3 state-owned companies in the city of Bandung. The method used in this research is a descriptive and verification method with a quantitative approach. The unit of observation is the managers of BUMN companies in the city of Bandung as many as 30 respondents. The statistical technique used in the analysis of the research data is the multiple regression method using the SPSS version 23 application. Based on the results of the analysis it is known that the quality of the management accounting information system, work motivation, and managerial performance at BUMN companies in the city of Bandung has been running very well. The results of the study show that the quality of management accounting information systems has no effect on managerial performance in BUMN companies in the city of Bandung. Meanwhile, work motivation influences managerial performance in BUMN companies in the city of Bandung.